Analysis of Indonesian Language Errors New Student Admission Technical Socialization Letter - Azis, Ahmad Ridhai; Abduh, Nurul Khairani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to describe Indonesian language errors contained in the 2023 STAIN Majene New Student Admission Socialization Letter and the factors that cause or influence Indonesian language errors in the letter. This research uses a qualitative paradigm by paying attention to syntax, and spelling of writing official letters. The results of this study are, (1) Indonesian language errors in the Technical Socialization Letter for New Student Admissions STAIN Majene there are errors in the level of syntax and spelling, and (2) The factors that cause or influence these errors are the lack of adequate mastery of Indonesian (according to EBI), the understanding of the letter writer does not attach importance to writing according to spelling (which is important the intention is conveyed) or there is no motivation to respond to the advice of the DinasÂ  Pendidikan dan Kebudayaan in 2015 on languages (Preserving Regional Languages, Prioritizing Indonesian, and Mastering Foreign Languages), there has never been an official letter writing training/workshop at STAIN Majene, and the language of letter writers is also influenced by the mother tongue (regional language). The suggestion in this study is that it is hoped that soon official letter writing training and socialization of the use of Indonesian Spelling (EBI) is valid in 2015-present.